Pattern of cancer in young adults at National Institute of Cancer Research and Hospital (NICRH), Bangladesh (Mymensingh Medical Journal, 2008)
Mymensingh Med J. 2007 Jul;16(2 Suppl):S28-33The abstract of this article is available on the PubMed website